DOI: 10.31274/rtd-180813-9324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental conditions on velvetleaf and giant foxtail epicuticular wax quantity and quality and the relationship to herbicide penetration

Abstract: Pitty, Abelino, "Effect of environmental conditions on velvetleaf and giant foxtail epicuticular wax quantity and quality and the relationship to herbicide penetration " (1988). Retrospective Theses and Dissertations. 9716.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Control velvetleaf produced 5.3 and 4.8 g of dry weight for velvetleaf subjected to -0.03 and -0.4 MPa \(fP, respectively. Drought stress has been reported to increase epicuticular leaf wax production (8,14,16). Recent data, however, suggest that epicu ticular leaf wax is not an effective barrier for U A N (18).…”
Section: Adjuvant Typementioning
confidence: 99%
See 2 more Smart Citations
“…Control velvetleaf produced 5.3 and 4.8 g of dry weight for velvetleaf subjected to -0.03 and -0.4 MPa \(fP, respectively. Drought stress has been reported to increase epicuticular leaf wax production (8,14,16). Recent data, however, suggest that epicu ticular leaf wax is not an effective barrier for U A N (18).…”
Section: Adjuvant Typementioning
confidence: 99%
“…Reasons for this reduction, however, are not well understood. Pitty (16) found that bentazon penetration was reduced in drought-stressed velvetleaf. Drought stress reduced acifluorfen {5-[2-chloro-4-(trifluoromethyl) phenoxy]-2-nitrobenzoic acid} activity (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scintillation cocktail best suited to quantify radioactivity for each herbicideweed treatment was determined based on both manufacturer's recommendations and maximum count efficiency (Table 1). Product A was similar to the scintillation cocktail used as a leaf wash by Pitty (1988) who reported that the cocktail was a 3:1 (v/v) mixture of xylene and Triton X-114 (octylphenoxypolyethoxyethanol) with 2,5-diphenyloxazole (PPO) added at 4 g/L.…”
Section: Methodsmentioning
confidence: 99%
“…The methods of 14 C-herbicide application and quantification were essentially consistent among researchers. However, the leaf wash methods utilized different compounds, including chloroform (Hinz and Owen 1996;Levene and Owen 1995), toluene-ethanol mixture (Olsen and Nalewaja 1982), methanol (Breeze et al 1992;Feng et al 1998), ethanol (Mabb and Price 1986;Price 1982), Triton 4 X-100 (Hageman and Behrens 1984), and xylene-Triton X-114 mixture (scintillation cocktail) (Pitty 1988). Historically, all methods, except the scintillation cocktail mixture, have been acceptable.…”
Section: Introductionmentioning
confidence: 99%